2002
DOI: 10.1093/ajcn/76.5.911
|View full text |Cite
|
Sign up to set email alerts
|

Fructose, weight gain, and the insulin resistance syndrome,,

Abstract: This review explores whether fructose consumption might be a contributing factor to the development of obesity and the accompanying metabolic abnormalities observed in the insulin resistance syndrome. The per capita disappearance data for fructose from the combined consumption of sucrose and high-fructose corn syrup have increased by 26%, from 64 g/d in 1970 to 81 g/d in 1997. Both plasma insulin and leptin act in the central nervous system in the long-term regulation of energy homeostasis. Because fructose do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
687
1
26

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 896 publications
(730 citation statements)
references
References 114 publications
16
687
1
26
Order By: Relevance
“…In animal studies, increased intake of fructose has been found to cause insulin resistance or worsen existing insulin resistance (Blakely et al, 1981). In humans, the metabolic effect of increased fructose intake is not clear (Elliott et al, 2002). Hallfrisch et al (1983) have found that a diet containing 15% of energy as fructose has detrimental effects on glucose metabolism both in normal and hyperinsulinemic men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal studies, increased intake of fructose has been found to cause insulin resistance or worsen existing insulin resistance (Blakely et al, 1981). In humans, the metabolic effect of increased fructose intake is not clear (Elliott et al, 2002). Hallfrisch et al (1983) have found that a diet containing 15% of energy as fructose has detrimental effects on glucose metabolism both in normal and hyperinsulinemic men.…”
Section: Discussionmentioning
confidence: 99%
“…A confounding factor in the present study might have been the relatively high fructose intake per day. High fructose intake has been reported to lower circulating insulin concentrations (Elliott et al, 2002;Teff et al, 2004). In fact, fructose seems to be very poor in stimulating insulin secretion (Bray et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…We did not found any inducement of the expression of key enzymes involved in lipogenesis since HFF treatment did not increased FAS. However, the observed increase in the expression of DGAT2 -an enzyme which catalyses the final step of TG synthesis-could also be implicated in hepatic lipid accumulation, together with the fact that fructose is an excellent lipogenic substrate [12,41]. HF plus fructose diet induces a shift from microvesicular towards macrovesicular lipid storage as analysed by histology.…”
Section: Page 16 Of 42mentioning
confidence: 99%
“…Those metabolic disturbances have been associated with i.e. hypertriglyceridemia and steatosis, linked to an increased de novo lipogenesis [12,13], modification of the activity of enzymes involved in hepatic glucose metabolism and glucose uptake pathways [14,15] and activation of NADPH oxidase pathway [11].…”
Section: Introductionmentioning
confidence: 99%
“…131,132 In western Europe, unlike in the United States, high fructose corn syrup is not a commonly used sweetener. Thus, the origin of most free dietary fructose is fruits and vegetables and overall fructose intakes are lower than in the United States.…”
Section: Ldl Particle Sizementioning
confidence: 99%